The thermodynamics of Pr55(Gag)-RNA interaction regulate the assembly of HIV - Tanwar, Hanumant S. (PLoS Pathog, 2017)
The interactions that occur during HIV Pr55(Gag) oligomerization and genomic RNA packaging are essential elements that facilitate HIV assembly. However, mechanistic details of these interactions are not clearly defined. Here, we overcome previous limitations in producing large quantities of full-length recombinant Pr55(Gag) that is required for isothermal titration calorimetry (ITC) studies, and we have revealed the thermodynamic properties of HIV assembly for the first time. Thermodynamic analysis showed that the binding between RNA and HIV Pr55(Gag) is an energetically favourable reaction (ΔG<0) that is further enhanced by the oligomerization of Pr55(Gag). The change in enthalpy (ΔH) widens sequentially from: (1) Pr55(Gag)-Psi RNA binding during HIV genome selection; to (2) Pr55(Gag)-Guanosine Uridine (GU)-containing RNA binding in cytoplasm/plasma membrane; and then to (3) Pr55(Gag)-Adenosine(A)-containing RNA binding in immature HIV. These data imply the stepwise increments of heat being released during HIV biogenesis may help to facilitate the process of viral assembly. By mimicking the interactions between A-containing RNA and oligomeric Pr55(Gag) in immature HIV, it was noted that a p6 domain truncated Pr50(Gag Δp6) is less efficient than full-length Pr55(Gag) in this thermodynamic process. These data suggest a potential unknown role of p6 in Pr55(Gag)-Pr55(Gag) oligomerization and/or Pr55(Gag)-RNA interaction during HIV assembly. Our data provide direct evidence on how nucleic acid sequences and the oligomeric state of Pr55(Gag) regulate HIV assembly.